Avaliação do resto-ingesta de uma escola pública localizada na zona sul do município de São Paulo - FERREIRA, Daniele Pereira Alves; SANTOS, Dejanira Socorro dos; SANTOS, Gabriela Rodrigues Cardoso (238, 2023)
Verificar, avaliar e comparar com a literatura atual a quantidade de resto ingesta no jantar de unidade escolar na zona sul da cidade de São Paulo, realizando pesagem do resto ingesta durante 15 dias, avaliar o resto ingesta, comparar os resultados obtidos com a literatura disponível, analisar o desperdício junto ao cardápio fornecido.

Verify, evaluate and compare with the current literature the amount of leftovers ingested at dinner at a school unit in the south zone of the city of São Paulo, weighing the rest ingested during 15 days, evaluating the rest ingested, comparing the results obtained with the available literature , analyze the waste along with the menu provided.
Evaluation of rest-intake in a public school located in the southern zone of the city of São Paulo
Keywords: Alimentação escolar; Desperdício de alimentos; Pesquisa; Restos de alimentos; Ambiente e Saúde